2018
DOI: 10.1038/s41598-018-36191-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo time-harmonic ultrasound elastography of the human brain detects acute cerebral stiffness changes induced by intracranial pressure variations

Abstract: Cerebral stiffness (CS) reflects the biophysical environment in which neurons grow and function. While long-term CS changes can occur in the course of chronic neurological disorders and aging, little is known about acute variations of CS induced by intracranial pressure variations. Current gold standard methods for CS and intracranial pressure such as magnetic resonance elastography and direct pressure recordings are either expensive and slow or invasive. The study objective was to develop a real-time method f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
0
34
0
1
Order By: Relevance
“…It is worthwhile to note that our present study is not in conflict with previous studies reporting a positive correlation between brain stiffness and ICP or perfusion pressure. 28,29,37 As outlined above, we believe that our technique is insensitive to short-term transient tissue compression induced by CAP, while static changes in the effective compression modulus of the brain, e.g. related to hypercapnia or the Valsalva maneuver, could impact MRE values differently from the effect we report here.…”
Section: Discussionmentioning
confidence: 61%
“…It is worthwhile to note that our present study is not in conflict with previous studies reporting a positive correlation between brain stiffness and ICP or perfusion pressure. 28,29,37 As outlined above, we believe that our technique is insensitive to short-term transient tissue compression induced by CAP, while static changes in the effective compression modulus of the brain, e.g. related to hypercapnia or the Valsalva maneuver, could impact MRE values differently from the effect we report here.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, experimentally induced hypercapnia was associated with a synchronous increase in cerebral blood flow and CS, as revealed by MRE ( Hetzer et al, 2019 ) and THE ( Kreft et al, 2020 ). Previous work also revealed that the Valsalva maneuver causes an increase in CS on a short time scale in the order of seconds ( Tzschatzsch et al, 2018 ). Taken together, this previous evidence suggests that lower cerebral blood flow, as a result of dehydration, reduces CS, which is consistent with the observations made in our study.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, we investigate the effect of dehydration on CS using cerebral time-harmonic elastography (THE), which utilizes multifrequency vibrations induced in the brain by an external driver in combination with transtemporal ultrasound ( Tzschatzsch et al, 2018 ). Cerebral THE has several advantages over MRE such as being available at the bedside and providing instantaneous feedback, which facilitates identification of rapid CS changes.…”
Section: Introductionmentioning
confidence: 99%
“…These diverging reports highlight the complex nature of hydrocephalus; e.g. cytopathology such as periventricular edema and dysmyelination which may drive decreased stiffness ( Del Bigio et al, 2003 , Del Bigio, 2010 ), while elevated pressure, which can be intermittent but chronic in NPH, may drive increased stiffness ( Pong et al, 2017 , Tzschatzsch et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%